2017
DOI: 10.1158/1535-7163.mct-16-0291
|View full text |Cite
|
Sign up to set email alerts
|

15α-methoxypuupehenol Induces Antitumor Effects In Vitro and In Vivo against Human Glioblastoma and Breast Cancer Models

Abstract: Studies with 15α-methoxypuupehenol (15α-MP), obtained from the extracts of Hyrtios sp., identified putative targets that are associated with its antitumor effects against human glioblastoma (GBM) and breast cancer. In the human GBM (U251MG) or breast cancer (MDA-MB-231) cells, treatment with 15α-MP repressed pY705Stat3 (Signal Transducer and Activator of Transcription 3), pErk1/2 (extracellular signal-regulated kinase), pS147CyclinB1, pY507Alk (Anaplastic lymphoma kinase), and pY478ezrin levels, and induced pS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…How allicin increases SHP-1 activity remains to be elucidated in a future study. Many drugs have been shown to have anti-tumor effects independent of the p-JAKs Tyk2 and Src, which are the upstream kinases of STAT3 signaling [58,59]. However, we did not examine whether tumor indexes were changed following the phosphorylation of these protein kinases.…”
Section: Discussionmentioning
confidence: 99%
“…How allicin increases SHP-1 activity remains to be elucidated in a future study. Many drugs have been shown to have anti-tumor effects independent of the p-JAKs Tyk2 and Src, which are the upstream kinases of STAT3 signaling [58,59]. However, we did not examine whether tumor indexes were changed following the phosphorylation of these protein kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering research on the therapeutic benefits of ezrin inhibition in osteosarcoma (OS) initially identified two small molecules, NSC50787 and NSC668394, which both dephosphorylate ezrin at its Thr567 residue, leading to inactivation [ 23 , 31 ]. To date, NSC668394 has been reported to display anticancer activity in a variety of tumors including, OS, diffuse large B-cell lymphoma (DLBCL), glioblastoma, and breast cancer [ 21 , 23 , 32 , 33 ]. However, no prior studies had investigated the effects of small molecule inhibition of ERM proteins on RMS cell viability, metabolism, or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activation of CDK5 increases glycogen synthase kinase‐3β and suppresses the activity of extracellular signal‐regulated protein kinase (ERK) 1/2/cyclic AMP response element‐binding protein signaling following sevoflurane exposure (Liu et al, ). Since glycogen synthase kinase‐3β is a cell apoptosis signal (Wang et al, ) and phosphorylated ERK 1/2 (pERK1/2) is a mitogenic kinase, changes in their activities by CDK5 can reduce astrocytic differentiation and GFAP expression (Hilliard et al, ).…”
Section: Expression Of Gfap and Its Regulationmentioning
confidence: 99%